2007
DOI: 10.1007/s00455-007-9087-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Scintigraphic Assessment of Swallowing of Older Patients Admitted to a Tertiary Care Geriatric Ward

Abstract: This study aimed to verify if older patients admitted to a tertiary care geriatric ward with no spontaneous complaints of dysphagia have impaired swallowing function as detected by a specialized clinical assessment and a scintigraphic study of swallowing. Thirty patients (mean age = 76.2 years, 17 women), consecutively admitted for the treatment of acute or chronic diseases, were studied. Two control groups were also studied, one consisting of 10 healthy older persons (mean age = 69.6 years, 5 women) and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…In contrast, other authors considered age as a predictor of dysphagia [18,25,26], with an increased risk of aspiration with advancing age [27]. …”
Section: Discussionmentioning
confidence: 97%
“…In contrast, other authors considered age as a predictor of dysphagia [18,25,26], with an increased risk of aspiration with advancing age [27]. …”
Section: Discussionmentioning
confidence: 97%
“…Clearance was the total exposure of an ROI to the bolus, which represents the interval between the arrival of the bolus head in the ROI and the departure of the bolus tail from the ROI. The definitions of these ROIs and of the measurements performed have been described and depicted previously [9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…However, a follow-up survey at acute care hospitals and inhome care centers found that, while not significant, one predictor variable of aspiration pneumonia was sex, with women seeming to have a slight disadvantage over men [28]. In addition, a study of swallowing function among volunteers and general acute phase patients reported that younger volunteer had significantly better swallowing function [29]. On the other hand, many studies of patients with cerebrovascular disorders have reported no significant differences in swallowing function [18][19][20], which indicates some variability due to disease and patient background.…”
Section: Discussionmentioning
confidence: 92%